Loss of FGFR3 Delays Acute Myeloid Leukemogenesis by Programming Weakly Pathogenic CD117-Positive Leukemia Stem-Like Cells - Guo, Chen; Ran, Qiuju; Sun, Chun; Zhou, Tingting; Yang, Xi; Zhang, Jizhou; Pang, Shifeng; Xiao, Yechen (Frontiers in Pharmacology, 2021)
Chemotherapeutic patients with leukemia often relapse and produce drug resistance due to the existence of leukemia stem cells (LSCs). Fibroblast growth factor receptor 3 (FGFR3) signaling mediates the drug resistance of LSCs in chronic myeloid leukemia (CML). However, the function of FGFR3 in acute myeloid leukemia (AML) is less understood. Here, we identified that the loss of FGFR3 reprograms MLL-AF9 (MA)-driven murine AML cells into weakly pathogenic CD117-positive leukemia stem-like cells by activating the FGFR1-ERG signaling pathway. FGFR3 deletion significantly inhibits AML cells engraftment in vivo and extends the survival time of leukemic mice. FGFR3 deletion sharply decreased the expression of chemokines and the prolonged survival time in mice receiving FGFR3-deficient MA cells could be neutralized by overexpression of CCL3. Here we firstly found that FGFR3 had a novel regulatory mechanism for the stemness of LSCs in AML, and provided a promising anti-leukemia approach by interrupting FGFR3.